2007
DOI: 10.1007/s10071-007-0117-0
|View full text |Cite
|
Sign up to set email alerts
|

Observational learning from tool using models by human-reared and mother-reared capuchin monkeys (Cebus apella)

Abstract: Studies of wild capuchins suggest an important role for social learning, but experiments with captive subjects have generally not supported this. Here we report social learning in two quite different populations of capuchin monkeys (Cebus apella). In experiment 1, human-raised monkeys observed a familiar human model open a foraging box using a tool in one of two alternative ways: levering versus poking. In experiment 2, mother-raised monkeys viewed similar techniques demonstrated by monkey models. A control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 42 publications
4
40
2
3
Order By: Relevance
“…If captive vervets are generally successful in opening the boxes during their first attempt with or without prior demonstrations, the results would support the hypothesis that exposure to human structures provides an environment that is likely to enculturate primates in a way that makes them more apt at solving technical problems. The ability to solve technical problems may also enable primates to perform better at other cognitive processes, and hence may facilitate imitation or other relatively sophisticated social learning mechanisms [Fredman and Whiten, 2008]. Such potential cross-links between cognitive domains deserve more attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If captive vervets are generally successful in opening the boxes during their first attempt with or without prior demonstrations, the results would support the hypothesis that exposure to human structures provides an environment that is likely to enculturate primates in a way that makes them more apt at solving technical problems. The ability to solve technical problems may also enable primates to perform better at other cognitive processes, and hence may facilitate imitation or other relatively sophisticated social learning mechanisms [Fredman and Whiten, 2008]. Such potential cross-links between cognitive domains deserve more attention in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, captive capuchin monkeys that have contact with a larger set of objects and more 'leisure' time to manipulate them exhibit an even broader range of object manipulation and tool use behaviours than their wild congeners [Beck, 1980;Gibson, 1990;Visalberghi, 1990;Fragaszy et al, 2004]. Further experiments have shown that human-reared capuchins behaved better in relation to social learning of tool use than individuals that were mother reared [Fredman and Whiten, 2008]. Together, these experiments suggest that the cognitive abilities of adult primates may depend on experimentally induced variation in environmental conditions during development.…”
Section: Introductionmentioning
confidence: 99%
“…Not all species may be able to view humans in this manner, although studies of fairness in non-human primates and object manipulation in crows demonstrate its plausibility as a mechanism [51,52]. In some primate cases, the positive effect of human interaction on animal tool use has been directly observed, for example in human-raised capuchin monkeys [53], and in wild vervet monkeys that were in regular contact with humans and human facilities [54]. Experiments with captive orangutans, bonobos and other great apes [55] and non-tool-using tamarins and marmosets [56] demonstrate that human-directed training on tool-use tasks enhances performance, which might be expected for any animal amenable to operant conditioning.…”
Section: (B) Factors Promoting Captivity Biasmentioning
confidence: 99%
“…Interpretation of these studies has always been muddied by the possibility that rearing differences, rather than phylogenetic differences, were responsible for the monkeys' failure to imitate a human demonstrator [see Call & Tomasello, 1996 for a similar view]. Custance et al [1999] and Fredman and Whiten [2008] focused on a more promising comparison group, human-reared capuchin monkeys. In Custance et al's paradigm, capuchin monkeys watched a human opening a box containing food.…”
Section: Introductionmentioning
confidence: 97%